ANALYSIS AND DESIGN OF LIBRARY INFORMATION SYSTEM AT MADRASAH AL - ITQON - Ari Irawan; Pramitha Dwi Larasati; Muhammad Fahrur Rasyaa (Universitas Tridharma, 2020)
Madrasah Al - Itqon started with the activities of ta'lim by KH Mahfudz Asirun, whichlater increased the number of congregations and reached all levels of society. He founded areligious education institution called Madrasah Al - Itqon in Duri Kosambi Village, CengkarengDistrict, West Jakarta, in 1985. The education cannot be separated from the existence of acollection of library materials that he owns. Some of the problems that often arise in librarymanagement are increasing or increasing library materials collection, the need for informationrelated to existing library materials, and library service personnel limitations. This researchaims to create a library information system to improve library visitors' full service and minimizedata processing errors. The library information system starts with data collection on members,borrowing books, and returning books. This library information system's benefits are expected toimprove library users' services and expedite the administrative process faster. Keywords- Information Systems, Libraries, Library Information System